Mass occurrence of the allozyme spectra changes in clonal spined loaches of the genus Cobitis caused by the anthropogenic pollution of the habitat - Mezhzherin, S.V.; Saliy, T.V.; Mezhzherin, I.S.; Losev, A.A.; Tsyba, A.A. (Reports of the National Academy of Sciences of Ukraine, 2018)
The unique record of mass anomalies of allozyme spectra has been found in the Irpin river in some cloning biotypes of spined loaches of the genus Cobitis. Evident predominance of genetically abnormal polyploidy loaches was occurred in the lower and middle streams of the river. While, in the upper part of this river, such individuals were extremely few in number. The reason for such genetic disorder is more likely an influence of toxic substances on the genetic apparatus, which have been accumulated in the low stream of this regulated river. Such an interpretation was confirmed by the results of bioindication. It shows an oppressed state of biota in the low part of the Irpen river basin. This is evident from the total absence of filter feeders-mollusks (family Unionidae) in this part of the river. Such mollusks are reliable indicators of a chemical pollution. Compared with the upper part of the Irpen river, there is a full range of species belonging to the family Unionidae, including even Unio crassus, U. tumidus, and Pseudoanadonta complanata, which almost extinct from the other rivers of modern Ukraine. In upper part of the river, a significantly higher degree of infection of the blood parasites Trypanosoma cobitis, carriers of which are freshwater leeches, is observed.